A melt-diffusion strategy for tunable sulfur loading on CC@MoS2 for lithium–sulfur​ batteries. (December 2020) - Tian, Chengxiang; Wu, Juwei; Ma, Zheng; Li, Bo; Zhang, Xu; Zu, Xiaotao; Xiang, Xia; Li, Sean
Abstract: For lithium–sulfur batteries, 3D cathodes might be of interest for containing the active material and trapping the polysulfides during cycling, owing to their binder-free and freestanding features. In this work, the MoS2 grown on the 3D structured Carbon Cloth (CC@MoS2 ) is firstly used to fabricate the Li–S battery and the sulfur loading can be freely tuned by adjusting thermal annealing time at 200 °C. A two-step melt-diffusion strategy is reported for fabrication of cathodes, which involves in melting and diffusion of sulfur covered by CC@MoS2 composites instead of dissolution of sulfur in the toxic organic solvents. Compared with the non-polar carbon cloth, the CC@MoS2 composites exhibit better adsorption capacity for polysulfides due to more edge active sites, which could effectively facilitate polysulfide redox kinetics. The SEM images of the CC@MoS2 cathode after 300 cycles show that MoS2 can still maintain the nanosheet morphology. After 300 cycles at 0.5 C, the CC@MoS2 cathodes loaded with 2 mg sulfur exhibit a better reversible capacity of 698 mA h g −1 compared with CC@MoS2 loaded with 1 mg sulfur (604 mA h g −1 ) and CC@MoS2 loaded with 4 mg sulfur (420 mA h g −1 ). This work proposes an environmentally friendly method to fabricate the lithium–sulfur battery cathode material and the sulfur loading can be freely adjusted. Graphical abstract: Highlights: The CC@MoS2 composite is firstly used to fabricate the Li–S battery. We present a low-cost two-step melt-diffusion strategy for fabrication of cathodes. The MoS2 can still maintain the nanosheet morphology after 300 cycles.